2019
DOI: 10.1111/aos.14277
|View full text |Cite
|
Sign up to set email alerts
|

The national comprehensive cancer network distress thermometer as a screening tool for the evaluation of quality of life in uveal melanoma patients

Abstract: Purpose: To assess quality of life (QoL) status via the National Comprehensive Cancer Network (NCCN) distress thermometer as a psychooncological screening tool in uveal melanoma patients. Methods: One hundred and six consecutive patients suffering from uveal melanoma completed the distress thermometer between 04/2018 and 12/2018. Practical, emotional, family concerned, spiritual, physical and overall distress levels, distribution of distress and subgroup analyses defining groups of potential high distress leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
2
8
1
Order By: Relevance
“…In a recent US American study, only a small percentage of uveal melanoma patients reported an existing offer of psychological support and there was vast dissatisfaction with psychological counseling. 3 The percentage of patients that reported pre-existing psychological support was similar to our study (13.3% versus 10.4% of patients 12 ). Yet, reportedly, only a limited number of patients suffering from distress accepts referrals to or turns to psycho-oncological support services with predictors and barriers to psychooncological support service utilization being understudied.…”
Section: Figuresupporting
confidence: 85%
See 3 more Smart Citations
“…In a recent US American study, only a small percentage of uveal melanoma patients reported an existing offer of psychological support and there was vast dissatisfaction with psychological counseling. 3 The percentage of patients that reported pre-existing psychological support was similar to our study (13.3% versus 10.4% of patients 12 ). Yet, reportedly, only a limited number of patients suffering from distress accepts referrals to or turns to psycho-oncological support services with predictors and barriers to psychooncological support service utilization being understudied.…”
Section: Figuresupporting
confidence: 85%
“…Details on descriptive patient data, best corrected visual acuity (BCVA) evaluation and calculation of the receiver operating characteristic (ROC)-threshold of the NCCN distress thermometer can be found in Klingenstein et al 2020. 12 This study now adds the important calculation of concrete predictive risk factors of uveal melanoma patients to develop psycho-oncological distress in need of treatment by multivariate correlations and multiple linear regression analysis for clinical routine practice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[26] McFarland et al reported that 40% of patients with breast cancer had fatigue, the most common physical problem associated with distress. [27] Unlike previous studies, [28,29] in this study nancial di culty was the highest-ranking single item associated with distress. The prevalence of psychological distress and nancial toxicity was 56.5% and 53.1%, respectively.…”
Section: Discussioncontrasting
confidence: 64%